2017
DOI: 10.1080/14767058.2016.1242122
|View full text |Cite
|
Sign up to set email alerts
|

Budget impact analysis of sFlt-1/PlGF ratio as prediction test in Italian women with suspected preeclampsia

Abstract: Introduction of sFlt-1/PlGF into hospital practice is cost-saving. Savings are generated primarily through improvement in diagnostic accuracy and reduction in unnecessary hospitalization for women before PE's onset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…However, the use of angiogenic factors in high‐risk populations (women who present with signs or symptoms of PE) may confer significant economic benefit . Various studies have suggested savings using the sFlt‐1/PlGF ratio of £334/patient (UK), £945/patient (UK); €670/patient (Italy), and using PlGF alone of £35 087/1000 patients (UK) …”
Section: Economic Modelling/potential Economic Impactmentioning
confidence: 99%
“…However, the use of angiogenic factors in high‐risk populations (women who present with signs or symptoms of PE) may confer significant economic benefit . Various studies have suggested savings using the sFlt‐1/PlGF ratio of £334/patient (UK), £945/patient (UK); €670/patient (Italy), and using PlGF alone of £35 087/1000 patients (UK) …”
Section: Economic Modelling/potential Economic Impactmentioning
confidence: 99%
“…In this study, we have shown a modest cost‐saving in comparison with other studies . Previous health economic studies of the implementation of PlGF testing in clinical care were based on hypothetical assumptions of reduction in resource use, with greater cost‐savings than we have presented in this analysis.…”
Section: Discussionmentioning
confidence: 58%
“…National guidelines have approved PlGF testing to rule out suspected pre‐eclampsia in the UK . Hypothetical economic models have found that PlGF‐based testing gives a cost‐saving of between £330 and £1032 per woman tested . These models have not examined trial data where use of PlGF has been incorporated into clinical care.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in overall healthcare costs by 28% was observed. In particular, test implementation reduced 69.5% of unnecessary hospitalizations [22]. A similar cost--effectiveness study of PE testing in UK was published.…”
Section: A Short-term Prediction and Exclusion Of Pementioning
confidence: 84%